Reduction of Carbon-Burdened Chromite Pellets in the Presence of Additives - Guanghui Li; Jianchen Lim; Mingjun Rao; Guohua Bai; Tao Jiang (The Minerals, Metals and Materials Society, 2011)
"By using thermogravimetry, optical microscope and chemical phase analysis, the solid-state reduction of carbon-burdened chromite pellets in the absence and presence of additives were investigated. The effects of reduction temperature, reduction time and additives on the metallization of chromite pellet were studied. The results indicate that the pre-reduction ratio of carbon-burdened chromite pellets is improved with the increase of reduction temperature and the addition of additives. The metallization of chromium is increased from 63.9% to 92.8% at 1300 °C for 4h with the addition of 2 wt.% of sodium borate. Investigation suggests that the reduction of carbon-burdened chromite pellets is diffusion controlled. The apparent activation energy without additive is 192.1 kJ/mol, while it decreases to 170.4 kJ/mol in the present sodium borate.IntroductionFerrochrome is used to produce high strength, corrosion resistant, wear-resisting, high temperature resistant and oxidation resistant special steels, and it is becoming one of the most important alloy materials for the production of stainless and high alloying ferritic steels [1-5]. Demand for ferrochrome is steadily on the rise due to the growth of stainless steel industry. Nowadays, more than 80% of the world's ferrochrome is utilized in the production of stainless steel [6-7].Ferrochrome is mainly produced in submerged-arc furnaces (SAF) with chromite lump ore. However, lump ore merely accounts for 20% of the chromite ore output, while fine ore (< 8 mm) accounts for about 80% [8]. Therefore, agglomeration of chromite fine ore is necessary before charging into SAF."